Stromab - Gedanken zur Hermeneutik biblischer Texte im Kontext der neueren angelsächsischen Diskussion - Loader, James Alfred (Verbum et ecclesia, 2000)
Downstream - On Biblical hermeneutics in the context of the recent Anglo-Saxon debate This paper, delivered at the 2000 meeting of the Rudolf Bultmann Society at Hofgeismar in Germany, offers a survey of recent developments in literary criticism in the English-speaking world. Contributions to the systematic reflection on issues relevant for theology are also considered and the author’s own proposal is outlined. It is argued that the hermeneutic character of theology remains necessary in the Christian tradition. This is, however, not founded on the proposition of the linguistic nature of revelation, but on the fact that theology is the reflective human speaking about God.